The stress signalling pathway nuclear factor E2-related factor 2 is activated in the liver of sows during lactation - Rosenbaum, Susann; Ringseis, Robert; Hillen, Sonja; Becker, Sabrina; Erhardt, Georg; Reiner, Gerald; Eder, Klaus; Justus Liebig University Giessen (My University, 2012)
Background: It has recently been shown that the lactation-induced inflammatory state in the liver of dairy cows is accompanied by activation of the nuclear factor E2-related factor 2 (Nrf2) pathway, which regulates the expression of antioxidant and cytoprotective genes and thereby protects tissues from inflammatory mediators and reactive oxygen species (ROS). The present study aimed to study whether the Nrf2 pathway is activated also in the liver of lactating sows. Findings: Transcript levels of known Nrf2 target genes, UGT1A1 (encoding glucuronosyltransferase 1 family, polypeptide A1), HO-1 (encoding heme oxygenase 1), NQO1 (encoding NAD(P)H dehydrogenase, quinone 1), GPX1 (encoding glutathione peroxidase), PRDX6 (encoding peroxiredoxin 6), TXNRD1 (encoding thioredoxin reductase 1), and SOD (encoding superoxide dismutase), in the liver are significantly elevated (between 1.7 and 3.1 fold) in lactating sows compared to non-lactating sows. The inflammatory state in the liver was evidenced by the finding that transcript levels of genes encoding acute phase proteins, namely haptoglobin (HP), fibrinogen ? (FGG), complement factor B (CFB), C-reactive protein (CRP) and lipopolysaccharide-binding protein (LBP), were significantly higher (2 to 8.7 fold) in lactating compared to non-lactating sows. Conclusions: The results of the present study indicate that the Nrf2 pathway in the liver of sows is activated during lactation. The activation of Nrf2 pathway during lactation in sows might be interpreted as a physiologic means to counteract the inflammatory process and to protect the liver against damage induced by inflammatory signals and ROS.
Keywords: ddc:630